Aromatase Activity After a Short-course of Letrozole Administration in Adult Men at Sea Level and at High Altitude (with or without Excessive Erythrocytosis) - Gonzales, G. F.; Tapia, V.; Gasco, M.; Gonzales-Castañeda, C. (Hormone and Metabolic Research, 2012)
Men living at high altitudes in Peru compared to sea level counterparts have erythrocytosis (hemoglobin 16–21 g/dl) or excessive erythrocytosis (hemoglobin>21 g/dl). High testosterone (T) levels in men at high altitude (HA) were associated with excessive erythrocytosis. High androgen levels could be due to a low aromatase activity or to an elevated rate of conversion from precursors to testosterone. The aim of this study was to evaluate aromatase activity and rate of conversion from precursors to testosterone before and after administration of the aromatase enzyme inhibitor letrozole (5 mg/day) for a 5-day period to men at HA and at sea level (SL). The response to short term aromatase inhibition was assessed in 30 adult men living at sea level, 31 native men at HA with erythrocytosis (Hb 16–21 g/dl), and 35 men at HA with excessive erythrocytosis (Hb>21 g/dl). Serum hormone levels, estradiol/testosterone, testosterone/androstenedione, and testosterone/dehydroepiandrosterone sulfate (DHEAS) ratios were measured. Men with erythrocytosis had lower basal serum T/androstenedione ratios than men with excessive erythrocytosis at HA and men at sea level. Men at HA with excessive erythrocytosis had higher T/DHEAS ratios than men with erythrocytosis and than those at sea level before and after letrozole administration. After letrozole administration, both groups of men at high altitude (with erythrocytosis or with excessive erythrocytosis) showed lower aromatase activities than those at sea level. In conclusion, higher serum testosterone levels in men with excessive erythrocytosis were associated with an increased rate of conversion from DHEAS to testosterone rather than to a lower aromatase activity.
Keywords: aromatase inhibition; altitude; testosterone; estradiol; DHEAS